Dinamika Sengketa Pemilihan Kepala Daerah Serentak di Indonesia untuk Mewujudkan Pemilihan Kepala Daerah yang Berintegritas: Studi di Kota Pematangsiantar dan Kabupaten Karo - Nofi Sri Utami; maurice rogers; Amelya Gustina; Rian Sacipto (Inovasi, 2025)
Direct regional head elections began on June 1, 2005, allowing people to elect their own regional leaders. Provincial, Regency, and City Election Commissions are given the authority to organize direct regional elections and are accountable to the DPRD. Overall, the implementation of direct regional elections demonstrates Indonesia's commitment to strengthening people's sovereignty and implementing democratic principles. The regional election disputes in Pematangsiantar City and Karo Regency in 2015 and 2020 demonstrate the complexity of local political dynamics. The dispute in Pematangsiantar City began when the KPU disqualified one of the candidate pairs in the 2015 regional election, causing delays and dissatisfaction that continued until the 2020 regional election. Meanwhile, in Karo Regency, the 2015 and 2020 regional election disputes included allegations of campaign violations and vote manipulation, which were brought to the Constitutional Court but did not change the final results. These disputes reflect the challenges in implementing local democracy and the need for improvements in dispute resolution mechanisms to maintain integrity and public trust. The research method used is the normative-empirical legal research method. The data collection method uses literature study and interviews. This research is a qualitative research. Analysis is carried out on data from preliminary studies or secondary data. Qualitative data analysis during the field uses the Miles and Huberman Model analysis, namely data reduction, data models, drawing/verifying conclusions. In this qualitative research, data analysis has been carried out simultaneously with the data collection process. The recommendation of this research is that all elements, both society, government, NGOs, tribal leaders, must work together to realize elections with integrity. because elections with integrity are not only seen from the results but the process/stages must also have integrity. Keywords : Indonesian democracy, Pancasila, 1945 Constitution, Elections, Pilkada